2017
DOI: 10.1002/eqe.2992
|View full text |Cite
|
Sign up to set email alerts
|

Empirical‐based out‐of‐plane URM infill wall model accounting for the interaction with in‐plane demand

Abstract: Summary The role of masonry infills in the seismic behavior of reinforced concrete buildings has been widely studied in terms of their strength and stiffness contribution in the in‐plane (IP) direction, while fewer studies have been carried out on their response and modeling in the out‐of‐plane (OOP) direction. In this paper, the state of the art in code and literature provisions regarding infills' OOP capacity and seismic demand is presented, together with a review of the experimental tests that have been car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 33 publications
(85 reference statements)
3
57
1
Order By: Relevance
“…Flanagan and Bennett [8,9] performed a series of tests on masonry infilled steel frames under pure OOP, different sequential, and combined bidirectional loadings to investigate the interaction effects in two directions and proposed a prediction for the OOP strength. Similar experimental studies were also performed by Calvi and Bolognini [10], Kuang and Yuen [11], Pereira et al [12], Hak et al [13], and Ricci et al [14] to further investigate the IP and OOP interaction in infilled RC frames. ese experimental programs have demonstrated that the damage in one direction has a detrimental effect on the response of infilled frames in the other direction, and the detrimental effect increases as the damage in one direction increases.…”
Section: Introductionsupporting
confidence: 62%
“…Flanagan and Bennett [8,9] performed a series of tests on masonry infilled steel frames under pure OOP, different sequential, and combined bidirectional loadings to investigate the interaction effects in two directions and proposed a prediction for the OOP strength. Similar experimental studies were also performed by Calvi and Bolognini [10], Kuang and Yuen [11], Pereira et al [12], Hak et al [13], and Ricci et al [14] to further investigate the IP and OOP interaction in infilled RC frames. ese experimental programs have demonstrated that the damage in one direction has a detrimental effect on the response of infilled frames in the other direction, and the detrimental effect increases as the damage in one direction increases.…”
Section: Introductionsupporting
confidence: 62%
“…More recently, some refined strut models have also been proposed to simulate the out-of-plane response of IRCFSs and the interaction between in-plane and out-of-plane responses of masonry infills. [35][36][37][38] To overcome some of the limits of the (in-plane) strut model, an alternative model of the infill was recently proposed by Caliò and Pantò 39 and denoted as discrete macro-element model (DMEM). In this latter proposal, the infill was simulated by means of a plane, geometrically consistent, mechanical model able to reproduce the non-linear behaviour of unreinforced masonry panels.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, often the proposed modifications appear unsuitable to be applied in a general view because based on empirical formulations obtained from a restricted number of laboratory tests. More recently, some refined strut models have also been proposed to simulate the out‐of‐plane response of IRCFSs and the interaction between in‐plane and out‐of‐plane responses of masonry infills …”
Section: Introductionmentioning
confidence: 99%
“…6 Similar experiments have been carried out on thick and thin traditional (both unreinforced and reinforced) and strengthened MIs. 24 Among the micro-models that are easier to calibrate, a fibresection interaction in tension and compression is implemented in Kadysiew et al, 25 with two beam-column elements placed along a single diagonal and joined at the midpoint node where a lumped mass in the OOP direction is assumed. Experimental characterization of the monotonic and cyclic OOP capacity of medium typology with single and double-leaf MIs, with and without previous IP cyclic damage, has also been performed.…”
mentioning
confidence: 99%
“…22 Given numerical problems of this approach, two macro-models have recently been proposed: ie, four diagonal struts having rigid behaviour and one central element focusing the non-linear IP and linear OOP responses 23 ; a single diagonal strut with lumped plasticity at the midpoint node. 24 Among the micro-models that are easier to calibrate, a fibresection interaction in tension and compression is implemented in Kadysiew et al, 25 with two beam-column elements placed along a single diagonal and joined at the midpoint node where a lumped mass in the OOP direction is assumed. A more practical version of the previous model has been employed in Mosalam and Gunay, 26 considering beams with plastic hinges where non-linear fibres are located along a line in the transversal direction so that truss and flexural behaviour are obtained in the IP and OOP directions, respectively.…”
mentioning
confidence: 99%